Synthesis of enantiomers of 3-methyl- and 3-phenyl-3, 4-dihydro-2H-[1, 4]benzothiazines and their 1, 1-dioxides via an acylative kinetic resolution protocol. Issue 4 (28th February 2015) - Gruzdev, Dmitry A.; Chulakov, Evgeny N.; Sadretdinova, Liliya Sh.; Kodess, Mikhail I.; Levit, Galina L.; Krasnov, Victor P.
Graphical abstract